Synthesis of 5H-Pyrrolo[3,4-b]pyrazine-Based Peptidomimetics - Biitseva, Angelina V.; Rudenko, Igor V.; Hordiyenko, Olga V.; Omelchenko, Iryna V.; Arrault, Axelle (Synthesis, 2015)
A range of 5H-pyrrolo[3,4-b]pyrazine-based peptidomimetics were designed, and their efficient synthesis starting from 5-imino-5H-pyrrolo[3,4-b]pyrazin-7-amine by subsequent interaction with N-protected amino acid hydrazides and amino acid esters with N,N-carbonyldiimidazole as the coupling agent was elaborated.
Keywords: amino acids; peptidomimetics; nitrogen heterocycles; coupling; hydrazones; ureas